Pengembangan Video Pembelajaran Sparkol Videoscribe dengan Model Pembelajaran Make A Match pada Materi Lingkaran di MTS Alkhairaat - Fitrianti Fitrianti (Program Studi Pendidikan Matematika, 2022)
This research is a development research that focuses on developing mathematics learning videos. This research was conducted at MTS Alkhairaat in class VIII. The results of this study, based on the make a match-based sparkol videoscribe learning video, obtained an average score of 3.79 with